2011
DOI: 10.1007/s00464-011-1657-6
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted intersphincteric resection for low rectal cancer: technique and short-term outcome for 29 consecutive patients

Abstract: Robot-assisted intersphincteric resection for very low rectal cancer is feasible, and its short-term outcome is acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 25 publications
3
40
0
Order By: Relevance
“…the docking time was reported in 4 studies with a median of 9.6 minutes. 23,36,37,42 the operating time still represents a disadvantage of robotic surgery; however, it might be overcome with an increased experience.…”
Section: Conversion Ratementioning
confidence: 99%
“…the docking time was reported in 4 studies with a median of 9.6 minutes. 23,36,37,42 the operating time still represents a disadvantage of robotic surgery; however, it might be overcome with an increased experience.…”
Section: Conversion Ratementioning
confidence: 99%
“…Although Baik et al reported that serious complication rates were significantly lower with robotic surgery (5.4 %) compared with laparoscopic surgery (19.3 %) [15], complication rates did not differ between robotic and laparoscopic surgeries in other reports [9,11,14,16,19,25]. The results of meta-analyses have demonstrated that there is no difference in complication rates [20][21][22][23].…”
Section: Perioperative Complicationsmentioning
confidence: 85%
“…A number of reports have demonstrated a longer operation time with robotic surgery [9,[11][12][13], whereas others have reported no difference in operation time between robotic and laparoscopic surgeries [14][15][16][17][18]. Patriti et al reported a shorter operation time for robotic rectal resection; however, they are minority in this regard [19].…”
Section: Operation Timementioning
confidence: 98%
“…Baek and colleagues reported a series of 64-stage I-III cancer patients, who underwent robotic TME, where there were no positive circumferential margins; however, adequacy of the TME specimen was not reported 19 . Several series of robotic TME suggest adequate short-term outcomes, with operative times in the neighbourhood of 300 minutes, low or zero positive margin rates and acceptable rates of anastomotic leak of 7%-10% 9,20 . A comparative study for TME found no difference in short-term outcomes or oncologic adequacy of the resected specimen compared to laparoscopic TME 21 .…”
Section: Rectal Resection and Total Mesorectal Excisionmentioning
confidence: 99%